Thinking About Thinking About Pain: Development of a Measure and Model of Pain-Related Metacognition - Schütze, Robert Michael (Curtin University, 2017)
Pain catastrophising (PC) is one of the strongest psychological predictors of negative pain outcomes. This thesis explores higher order beliefs, or metacognitions, underlying catastrophising using four linked studies: a systematic review of randomised trials measuring PC changes; a qualitative study of people with elevated PC; development and validation of the Pain Metacognitions Questionnaire; and a path analysis. Results support a repetitive negative thinking model of PC where unhelpful metacognitions are important moderators of catastrophising.